Anti-aging cable and preparation method thereof
By introducing epoxidized branched modified nanotitanium dioxide into the cable sheath material, the problem of cable resistance to UV aging in outdoor environments is solved, and the efficient anti-UV absorption and mechanical performance of the cable is achieved.
Patent Information
- Application Number
- CN202510670290.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-05-23
AI Technical Summary
Existing cables are prone to aging in outdoor environments, especially inadequate anti-ultraviolet aging ability, resulting in reduced insulation performance and weakened mechanical strength, posing safety hazards.
Epoxy branched modified nanotitanium dioxide is used as the sheath material. By introducing a naphthalene ring structure on the surface of the nanotitanium dioxide, its compatibility and dispersion with the polymer matrix are improved, and the ultraviolet absorption capacity is enhanced through epoxidation treatment.
It significantly improves the cable's anti-ultraviolet aging performance, reduces the degree of yellowing, maintains stable mechanical properties, and extends service life.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to an aging-resistant cable and a preparation method thereof. Background Art
[0002] With the development of modern industry and social infrastructure, cables, as crucial carriers of energy transmission and information communication, are facing ever-increasing performance requirements. This is particularly true in outdoor environments, where cables are exposed to harsh conditions such as UV radiation, temperature fluctuations, and rainwater erosion, making them susceptible to aging. Cable aging not only manifests itself as yellowing and cracking, but more seriously, it can lead to a decline in insulation performance, weakened mechanical strength, and even safety incidents. Therefore, improving cable aging resistance, particularly resistance to UV aging, is crucial for ensuring the stable operation of power systems and communication networks.
[0003] Traditional cable sheath materials typically use polymers such as polyethylene and polyvinyl chloride. These materials are susceptible to photooxidation in the natural environment, leading to molecular chain breakage, crosslinking, or degradation, which in turn degrades material performance. To address this issue, the industry often uses antioxidants and UV absorbers to improve the polymer's aging resistance. However, these small molecule additives often suffer from migration, volatilization, and precipitation, significantly reducing their protective effectiveness over time.
[0004] In recent years, nanomaterials, especially nano-titanium dioxide, have attracted widespread attention in the field of cable sheath anti-aging due to their excellent UV absorption capacity and chemical stability. Nano-titanium dioxide can effectively absorb and scatter UV rays and can theoretically be used as a highly effective anti-aging filler. However, in practical applications, nano-titanium dioxide faces key technical challenges such as poor dispersibility and poor interfacial compatibility. Due to the high activity of the nano-titanium dioxide surface, particles easily agglomerate, resulting in uneven dispersion, which not only reduces the UV absorption efficiency but may also cause a decrease in the mechanical properties of the material. In addition, the interfacial compatibility between nano-titanium dioxide and the polymer matrix is poor, which easily forms stress concentration points at the interface, making the material more prone to fracture under mechanical load. Summary of the Invention
[0005] In view of this, the object of the present invention is to provide an aging-resistant cable and a preparation method thereof, so as to improve the aging resistance of the cable, especially the resistance to ultraviolet light aging.
[0006] Based on the above purpose, the present invention provides an aging-resistant cable, which comprises, from the inside to the outside, a conductor, an insulation layer, a shielding layer and a sheath layer.
[0007] The insulating layer is a cross-linked polyethylene layer.
[0008] The shielding layer is a thick aluminum-plastic composite tape with tinned copper wires woven on the surface.
[0009] The sheath layer is prepared from the following raw materials in parts by weight: 70-90 parts of polyvinyl chloride resin, 4-6 parts of nitrile rubber, 4-6 parts of silicon dioxide, 0.5-2 parts of silane coupling agent and 15-25 parts of epoxidized branched modified nano titanium dioxide.
[0010] The polyvinyl chloride resin is a soft polyvinyl chloride resin.
[0011] The average particle size of the silicon dioxide is 5-20 μm.
[0012] The silane coupling agent is silane coupling agent KH-560.
[0013] The preparation steps of the epoxidized branched modified nano titanium dioxide are as follows: S1: Under a nitrogen atmosphere, nano-titanium dioxide, glycidol, and 3-(1-naphthyloxy)-1,2-epoxypropane are mixed, heated to 75-85°C, stirred and reacted for 1.5-2.5 hours, then heated to 95-105°C, stirred and reacted for 3-5 hours, and finally heated to 115-125°C, stirred and reacted for 1.5-2.5 hours, and cooled to obtain branched modified nano-titanium dioxide; S2: Under a nitrogen atmosphere, epichlorohydrin, triethylammonium chloride and branched modified nano-titanium dioxide are mixed, the temperature is raised to 75-85°C, stirred and reacted for 2-4 hours, then cooled to 55-65°C, an 8wt%-12wt% aqueous sodium hydroxide solution is added, the reaction is continued for 2-4 hours, the temperature is lowered, the mixture is allowed to stand, the precipitate is removed, and the mixture is rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide.
[0014] The average particle size of the nano-titanium dioxide in step S1 is 10-50 nm.
[0015] In step S1, the weight ratio of nano-titanium dioxide, glycidol and 3-(1-naphthyloxy)-1,2-epoxypropylene is 10-20:20-40:2-8.
[0016] In step S2, the weight ratio of epichlorohydrin, benzyltriethylammonium chloride, branched modified nano-titanium dioxide and sodium hydroxide aqueous solution is 100-200:0.3-0.8:40-60:20-30.
[0017] Furthermore, the present invention also provides a method for preparing an aging-resistant cable, comprising the following steps: (1) Polyethylene particles containing 2wt%-3wt% diisopropylbenzene peroxide crosslinking agent are extruded through an 80-100 mesh filter and wrapped on the surface of the conductor, with the extrusion thickness controlled to 1-2mm. Subsequently, the insulation layer is obtained by continuous vulcanization for 40-50min under the conditions of pressure 1-1.5MPa and temperature 205-210℃; (2) Wrap the insulation layer with a 0.1-0.15 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 25%-35%, and then weave a 0.1-0.2 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 85%-95% to obtain a shielding layer; (3) Add polyvinyl chloride resin, nitrile rubber, silica, silane coupling agent and epoxidized branched modified nano titanium dioxide into a mixer, heat to 80-90 ° C, stir at a speed of 1100-1300 rpm for 20-30 minutes to obtain a mixture, and finally put the mixture into a twin-screw extruder, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 1.8-2.2 mm, thus obtaining an aging-resistant cable.
[0018] In the step (3), the temperature of the first zone of the twin-screw extruder is 155-165°C, the temperature of the second zone is 170-180°C, and the temperature of the die head is 180-190°C.
[0019] Beneficial effects of the present invention: The aging-resistant cable provided by this invention achieves significant improvements in overall performance through the innovative application of epoxidized branched modified nano-titanium dioxide. The cable's sheath material exhibits an excellent balance of mechanical properties, with good tensile strength and extremely high elongation at break, enabling the cable to withstand various mechanical stresses without damage during installation and use.
[0020] The introduction of epoxidized branched modified nano-titanium dioxide not only enhances the cable's basic mechanical properties but, more importantly, imparts exceptional resistance to UV aging. This modified filler effectively absorbs and scatters UV radiation, interrupting the photooxidative degradation reaction chain and protecting the polymer matrix from UV damage. Even under long-term outdoor exposure conditions, the cable sheath maintains minimal yellowing, maintaining its original appearance, quality, and mechanical properties. This has significant practical value for cable products used outdoors.
[0021] The introduction of the naphthalene ring structure has a multi-faceted synergistic effect on the performance of the sheath material. First, the rigid structure of the naphthalene ring significantly enhances the surface stability of the nano-titanium dioxide and reduces the aggregation tendency of the nanoparticles. Second, the aromaticity of the naphthalene ring significantly enhances the ultraviolet absorption capacity of the entire system, acting as a highly effective light stabilizer to prevent photodegradation of the polymer chain. Furthermore, the larger steric hindrance of the naphthalene ring promotes the formation of a more open branched structure, further improving the dispersion of the nanoparticles in the polymer matrix. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.
[0023] In the specific embodiment of the present invention, the polyvinyl chloride resin is sourced from Sinopec Qilu Petrochemical Company, model QS-800F; nano-titanium dioxide is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with an average particle size of 25 nm and product number T104942; and nitrile rubber is purchased from Saikede (Hengshui) Rubber and Plastic Co., Ltd., with a brand name of LR820. Example
[0024] (1) Under nitrogen atmosphere, 10 g of nano-titanium dioxide, 20 g of glycidol and 2 g of 3-(1-naphthyloxy)-1,2-epoxypropane were mixed, heated to 75 °C, stirred and reacted for 1.5 h, then heated to 95 °C, stirred and reacted for 3 h, and finally heated to 115 °C, stirred and reacted for 1.5 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Under nitrogen atmosphere, 100 g of epichlorohydrin, 0.3 g of benzyltriethylammonium chloride and 40 g of branched modified nano-titanium dioxide were mixed, heated to 75 ° C, stirred and reacted for 2 h, then cooled to 55 ° C, 20 g of 8 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 2 h. The temperature was lowered, allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; (3) Polyethylene particles containing 2 wt% diisopropylbenzene peroxide crosslinking agent were extruded through an 80-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1 MPa and a temperature of 205 °C for 40 min. (4) Wrap the insulation layer with a 0.1 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 25%, and then weave a 0.1 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 85% to obtain a shielding layer; (5) Add 70g of polyvinyl chloride resin, 4g of nitrile rubber, 4g of silica (average particle size 10μm), 0.5g of silane coupling agent KH-560 and 15g of epoxidized branched modified nano-titanium dioxide into a mixer, heat it to 80℃, stir it at 1100rpm for 20min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 155℃, the temperature of zone 2 to 170℃, and the die head temperature to 180℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 1.8mm, and thus obtain an aging-resistant cable. Example
[0025] (1) Under nitrogen atmosphere, 15 g of nano-titanium dioxide, 30 g of propylene oxide and 5 g of 3-(1-naphthyloxy)-1,2-propylene oxide were mixed, heated to 80 ° C, stirred and reacted for 2 h, then heated to 100 ° C, stirred and reacted for 4 h, and finally heated to 120 ° C, stirred and reacted for 2 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Under nitrogen atmosphere, 150 g of epichlorohydrin, 0.5 g of benzyltriethylammonium chloride and 50 g of branched modified nano-titanium dioxide were mixed, heated to 80 ° C, stirred and reacted for 3 h, then cooled to 60 ° C, 25 g of 10 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 3 h. The temperature was lowered, allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; (3) Polyethylene particles containing 2.5 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 90-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1.5 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.2 MPa and a temperature of 210 °C for 45 min. (4) Wrap the insulation layer with a 0.12 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 30%, and then weave a 0.15 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 90% to obtain a shielding layer; (5) Add 80g of polyvinyl chloride resin, 5g of nitrile rubber, 5g of silica (average particle size 10μm), 1g of silane coupling agent KH-560 and 20g of epoxidized branched modified nano-titanium dioxide into a mixer, heat it to 85℃, stir it at 1200rpm for 25min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 160℃, the temperature of zone 2 to 175℃, and the die temperature to 185℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2mm, and thus obtain an aging-resistant cable. Example
[0026] (1) Under nitrogen atmosphere, 20 g of nano-titanium dioxide, 40 g of propylene oxide and 8 g of 3-(1-naphthyloxy)-1,2-propylene oxide were mixed, heated to 85 ° C, stirred and reacted for 2.5 h, then heated to 105 ° C, stirred and reacted for 5 h, and finally heated to 125 ° C, stirred and reacted for 2.5 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Under nitrogen atmosphere, 200 g of epichlorohydrin, 0.8 g of benzyltriethylammonium chloride and 60 g of branched modified nano-titanium dioxide were mixed, heated to 85 ° C, stirred and reacted for 4 h, then cooled to 65 ° C, 30 g of 12 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 4 h. The temperature was lowered, the mixture was allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; (3) Polyethylene particles containing 3 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 100-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 2 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.5 MPa and a temperature of 210 °C for 50 min. (4) Wrap the insulation layer with a 0.15 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 35%, and then weave a 0.2 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 95% to obtain a shielding layer; (5) Add 90g of polyvinyl chloride resin, 6g of nitrile rubber, 6g of silica (average particle size 10μm), 2g of silane coupling agent KH-560 and 25g of epoxidized branched modified nano-titanium dioxide into a mixer, heat it to 90℃, stir it at 1300rpm for 30min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 165℃, the temperature of zone 2 to 180℃, and the die head temperature to 190℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2.2mm, and thus obtain an aging-resistant cable.
[0027] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the 20g epoxidized branched modified nano-titanium dioxide in step (5) is replaced by 5g branched modified nano-titanium dioxide; The specific steps are as follows: (1) Under nitrogen atmosphere, 15 g of nano-titanium dioxide, 30 g of propylene oxide and 5 g of 3-(1-naphthyloxy)-1,2-propylene oxide were mixed, heated to 80 ° C, stirred and reacted for 2 h, then heated to 100 ° C, stirred and reacted for 4 h, and finally heated to 120 ° C, stirred and reacted for 2 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Polyethylene particles containing 2.5 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 90-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1.5 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.2 MPa and a temperature of 210 °C for 45 min. (3) Wrap the insulation layer with a 0.12 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 30%, and then weave a 0.15 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 90% to obtain a shielding layer; (4) Add 80g of polyvinyl chloride resin, 5g of nitrile rubber, 5g of silica (average particle size 10μm), 1g of silane coupling agent KH-560 and 5g of branched modified nano-titanium dioxide into a mixer, heat it to 85℃, stir it at 1200rpm for 25min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 160℃, the temperature of zone 2 to 175℃, and the die head temperature to 185℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2mm, and thus obtain a cable.
[0028] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the 3-(1-naphthyloxy)-1,2-epoxypropane in step (1) is replaced by glycidol; The specific steps are as follows: (1) Under nitrogen atmosphere, 15 g of nano-titanium dioxide and 35 g of glycidol were mixed, heated to 80 ° C, stirred and reacted for 2 h, then heated to 100 ° C, stirred and reacted for 4 h, and finally heated to 120 ° C, stirred and reacted for 2 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Under nitrogen atmosphere, 150 g of epichlorohydrin, 0.5 g of benzyltriethylammonium chloride and 50 g of branched modified nano-titanium dioxide were mixed, heated to 80 ° C, stirred and reacted for 3 h, then cooled to 60 ° C, 25 g of 10 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 3 h. The temperature was lowered, allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; (3) Polyethylene particles containing 2.5 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 90-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1.5 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.2 MPa and a temperature of 210 °C for 45 min. (4) Wrap the insulation layer with a 0.12 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 30%, and then weave a 0.15 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 90% to obtain a shielding layer; (5) Add 80g of polyvinyl chloride resin, 5g of nitrile rubber, 5g of silica (average particle size 10μm), 1g of silane coupling agent KH-560 and 20g of epoxidized branched modified nano-titanium dioxide into a mixer, heat it to 85℃, stir it at 1200rpm for 25min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 160℃, the temperature of zone 2 to 175℃, and the die temperature to 185℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2mm, and thus obtain a cable.
[0029] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that: 3-(1-naphthyloxy)-1,2-epoxypropane in step (1) is replaced by naphthalene; The specific steps are as follows: (1) Under nitrogen atmosphere, 15 g of nano-titanium dioxide, 30 g of glycidol and 5 g of naphthalene were mixed, heated to 80 ° C, stirred and reacted for 2 h, then heated to 100 ° C, stirred and reacted for 4 h, and finally heated to 120 ° C, stirred and reacted for 2 h, and cooled to obtain branched modified nano-titanium dioxide; (2) Under nitrogen atmosphere, 150 g of epichlorohydrin, 0.5 g of benzyltriethylammonium chloride and 50 g of branched modified nano-titanium dioxide were mixed, heated to 80 ° C, stirred and reacted for 3 h, then cooled to 60 ° C, 25 g of 10 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 3 h. The temperature was lowered, allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; (3) Polyethylene particles containing 2.5 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 90-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1.5 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.2 MPa and a temperature of 210 °C for 45 min. (4) Wrap the insulation layer with a 0.12 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 30%, and then weave a 0.15 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 90% to obtain a shielding layer; (5) Add 80g of polyvinyl chloride resin, 5g of nitrile rubber, 5g of silica (average particle size 10μm), 1g of silane coupling agent KH-560 and 20g of epoxidized branched modified nano-titanium dioxide into a mixer, heat it to 85℃, stir it at 1200rpm for 25min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 160℃, the temperature of zone 2 to 175℃, and the die temperature to 185℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2mm, and thus obtain a cable.
[0030] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the 20g epoxidized branched modified nano-titanium dioxide in step (5) is replaced by a mixture of 18.5g branched epoxy resin and 1.5g nano-titanium dioxide; The specific steps are as follows: (1) Under nitrogen atmosphere, 30 g of propylene oxide and 5 g of 3-(1-naphthyloxy)-1,2-propylene oxide were mixed, heated to 80°C, stirred and reacted for 2 h, then heated to 100°C, stirred and reacted for 4 h, and finally heated to 120°C, stirred and reacted for 2 h, and cooled to obtain a branched polyol; (2) Under nitrogen atmosphere, 150 g of epichlorohydrin, 0.5 g of benzyltriethylammonium chloride and 35 g of branched polyol were mixed, heated to 80 ° C, stirred and reacted for 3 h, then cooled to 60 ° C, 25 g of 10 wt% sodium hydroxide aqueous solution was added, and the reaction was continued for 3 h. The temperature was lowered, the mixture was allowed to stand, the precipitate was removed, and the mixture was rotary evaporated to obtain a branched epoxy resin; (3) Polyethylene particles containing 2.5 wt% diisopropylbenzene peroxide crosslinking agent were extruded through a 90-mesh filter and wrapped on the conductor surface, with the extrusion thickness controlled at 1.5 mm. Subsequently, the insulation layer was obtained by continuous vulcanization at a pressure of 1.2 MPa and a temperature of 210 °C for 45 min. (4) Wrap the insulation layer with a 0.12 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 30%, and then weave a 0.15 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 90% to obtain a shielding layer; (5) Add 80g of polyvinyl chloride resin, 5g of nitrile rubber, 5g of silica (average particle size 10μm), 1g of silane coupling agent KH-560, 18.5g of branched epoxy resin and 1.5g of nano-titanium dioxide into a mixer, heat it to 85℃, stir it at 1200rpm for 25min to obtain a mixture, and finally put the mixture into a twin-screw extruder, set the temperature of zone 1 to 160℃, the temperature of zone 2 to 175℃, and the die head temperature to 185℃, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 2mm, and thus obtain a cable.
[0031] Performance testing: Sample preparation and pretreatment: Take the cable samples prepared in Examples 1-3 and Comparative Examples 1-4, and use a dumbbell-shaped cutter to sample the sheath layer according to GB / T2951.11-2008 standard to prepare standard samples with a thickness of 2.0 mm. The standard samples are conditioned in an environment of 23±2°C and a relative humidity of 50±5% for 24 hours before testing.
[0032] Tensile Properties: Tested in accordance with GB / T 1040.3-2006 using a microcomputer-controlled electronic tensile testing machine. The tensile speed was 500 mm / min. The tensile strength and elongation at break were recorded. The results are shown in Table 1.
[0033] UV-accelerated aging test: In accordance with GB / T 16422.3-2014, dumbbell specimens of the cable sheath layer were subjected to a 21-day cyclic test (60°C illumination for 8 hours / 45°C condensation for 4 hours) using UVA-340 lamps (irradiance 0.76W / m²@340nm). Yellowing index and tensile strength were measured, and the tensile strength retention rate was calculated.
[0034] Table 1 Performance test results Tensile strength / MPa Elongation at break / % Tensile strength retention rate after light aging / % Yellowing index after photoaging Example 1 18.5 374 90.1 2.8 Example 2 20.3 365 92.5 2.5 Example 3 20.9 338 93.2 2.1 Comparative Example 1 22.3 275 86.3 4.8 Comparative Example 2 18.2 341 78.5 6.2 Comparative Example 3 17.1 315 80.8 5.8 Comparative Example 4 22.0 325 82.7 5.4 Data Analysis: The data from Examples 1-3 in Table 1 demonstrate that the aging-resistant cables prepared according to the present invention exhibit excellent overall performance. The cable's sheath material exhibits good tensile strength and extremely high elongation at break, a combination of mechanical properties demonstrating the material's combined strength and toughness. Furthermore, it exhibits excellent resistance to UV aging, with a very low yellowing index indicating that the material maintains excellent appearance quality even under long-term UV exposure, which is of great significance for cable products used outdoors.
[0035] As can be seen from the data of Example 2 and Comparative Example 1 in Table 1, although Example 2 has slightly lower tensile strength than Comparative Example 1, its elongation at break is significantly improved, and its performance after light aging is even better. This difference may be due to the increased amount of epoxidized branched modified nano-titanium dioxide used and the introduction of epoxidation treatment. The introduction of epoxy groups may have played a certain plasticizing role, resulting in the material showing a higher elongation at break.
[0036] From the data of Example 2 and Comparative Example 2 in Table 1, it can be seen that the introduction of the naphthalene ring structure may play a key role in many aspects: its rigid structure may enhance the stability of the surface of nano-titanium dioxide and reduce the aggregation tendency; its aromaticity may enhance the ability to absorb ultraviolet rays, playing an excellent light stabilizer role; its larger steric hindrance may help to form a more open branched structure, thereby improving the dispersibility of nanoparticles. During the photoaging process, the naphthalene ring structure may cooperate with titanium dioxide to absorb ultraviolet energy and dissipate it through thermal pathways, thereby avoiding energy transfer to the polymer chain and effectively blocking the photooxidative degradation reaction, thereby significantly improving the material's anti-ultraviolet aging performance and color stability.
[0037] From the data of Example 2 and Comparative Example 3 in Table 1, it can be seen that the 3-(1-naphthyloxy)-1,2-propylene oxide component has a positive effect on the modification of the surface structure of nano-titanium dioxide, and contributes significantly to the improvement of the material mechanics and weather resistance. The presence of the epoxy group plays a decisive role in the modification effect. This may be because the epoxy group has a high reactivity and can undergo a ring-opening reaction with the hydroxyl group in the branched structure to form a chemical bond, thereby achieving a more solid surface modification. In contrast, pure naphthalene molecules may only rely on physical adsorption to attach to the surface of the nanoparticles, with weak binding force and easy to fall off during processing and use.
[0038] As can be seen from the data of Example 2 and Comparative Example 4 in Table 1, Example 2 adopts epoxidized branched modified nano titanium dioxide, while Comparative Example 4 uses a simple mixture of branched epoxy resin and nano titanium dioxide. By directly carrying out branched modification and epoxidation treatment to nano titanium dioxide, a chemically bonded organic layer may be formed on the particle surface. This structure may be more conducive to preventing the agglomeration of nanoparticles in the polymer matrix, forming a more uniformly dispersed state. By contrast, the simple mixing in Comparative Example 4 may cause the nanoparticles to be unevenly dispersed, locally forming agglomerates, and reducing the effective area of interfacial interaction. The epoxidized branched modified treatment may form flexible molecular chains with multifunctional groups on the nanoparticle surface. These molecular chains can both interact with the polymer matrix and provide a certain plasticizing effect, thereby significantly improving the elongation at break while maintaining material strength. In addition, relative to direct mixing, titanium dioxide and naphthalene have closer contact in the epoxidized branched modified nano titanium dioxide, and may have played a more effective synergistic role in the light aging process, blocking free radical transmission and chain degradation reaction, thereby maintaining the mechanical properties of the material and alleviating the degree of yellowing.
[0039] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. An aging-resistant cable, characterized in that: From the inside to the outside, it includes conductor, insulation layer, shielding layer and sheath layer; The sheath layer is prepared from the following raw materials in parts by weight: 70-90 parts of polyvinyl chloride resin, 4-6 parts of nitrile rubber, 4-6 parts of silicon dioxide, 0.5-2 parts of silane coupling agent and 15-25 parts of epoxidized branched modified nano titanium dioxide; The preparation steps of the epoxidized branched modified nano titanium dioxide are as follows: S1: Under a nitrogen atmosphere, nano-titanium dioxide, glycidol, and 3-(1-naphthyloxy)-1,2-epoxypropane are mixed, heated to 75-85°C, stirred and reacted for 1.5-2.5 hours, then heated to 95-105°C, stirred and reacted for 3-5 hours, and finally heated to 115-125°C, stirred and reacted for 1.5-2.5 hours, and cooled to obtain branched modified nano-titanium dioxide; S2: Under a nitrogen atmosphere, epichlorohydrin, triethylammonium chloride and branched modified nano-titanium dioxide are mixed, the temperature is raised to 75-85°C, stirred and reacted for 2-4 hours, then cooled to 55-65°C, an 8wt%-12wt% sodium hydroxide aqueous solution is added, the reaction is continued for 2-4 hours, the temperature is lowered, the mixture is allowed to stand, the precipitate is removed, and the mixture is rotary evaporated to obtain epoxidized branched modified nano-titanium dioxide; In step S1, the weight ratio of nano-titanium dioxide, glycidol and 3-(1-naphthyloxy)-1,2-epoxypropylene is 10-20:20-40:2-8; In step S2, the weight ratio of epichlorohydrin, benzyltriethylammonium chloride, branched modified nano-titanium dioxide and sodium hydroxide aqueous solution is 100-200:0.3-0.8:40-60:20-30.
2. The aging-resistant cable according to claim 1, characterized in that: The insulating layer is a cross-linked polyethylene layer.
3. The aging-resistant cable according to claim 1, characterized in that: The shielding layer is a thick aluminum-plastic composite tape with tinned copper wires woven on the surface.
4. The aging-resistant cable according to claim 1, characterized in that: The polyvinyl chloride resin is a soft polyvinyl chloride resin.
5. The aging-resistant cable according to claim 1, characterized in that: The average particle size of the silicon dioxide is 5-20 μm.
6. The aging-resistant cable according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH-560.
7. A method for preparing an aging-resistant cable according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Polyethylene particles containing 2wt%-3wt% diisopropylbenzene peroxide crosslinking agent are extruded through an 80-100 mesh filter and wrapped on the surface of the conductor, with the extrusion thickness controlled to 1-2mm. Subsequently, the insulation layer is obtained by continuous vulcanization for 40-50min under the conditions of pressure 1-1.5MPa and temperature 205-210℃; (2) Wrap the insulation layer with a 0.1-0.15 mm thick aluminum-plastic composite tape in a spiral winding manner with an overlap rate of 25%-35%, and then weave a 0.1-0.2 mm diameter tinned copper wire on the surface with a braiding angle of 45° and a coverage rate of 85%-95% to obtain a shielding layer; (3) Add polyvinyl chloride resin, nitrile rubber, silica, silane coupling agent and epoxidized branched modified nano titanium dioxide into a mixer, heat to 80-90 ° C, stir at a speed of 1100-1300 rpm for 20-30 minutes to obtain a mixture, and finally put the mixture into a twin-screw extruder, extrude and wrap it on the surface of the shielding layer to form a sheath layer with a wall thickness of 1.8-2.2 mm, thus obtaining an aging-resistant cable.
8. The method for preparing an aging-resistant cable according to claim 7, characterized in that: In the step (3), the temperature of the first zone of the twin-screw extruder is 155-165°C, the temperature of the second zone is 170-180°C, and the temperature of the die head is 180-190°C.
Citation Information
Patent Citations
High-pressure-bearing branched epoxy resin plugging material and oil-based drilling fluid
CN116925498A
Resin composition, prepreg, and metal foil-clad laminate
US20150056454A1